Identification of Persistent Sulfidogenic Bacteria in Shale Gas Produced Waters - Cliffe, Lisa; Nixon, Sophie L.; Daly, Rebecca A.; Eden, Bob; Taylor, Kevin G.; Boothman, Christopher; Wilkins, Michael J.; Wrighton, Kelly C.; Lloyd, Jonathan R. (Frontiers in Microbiology, 2020)
Produced waters from hydraulically fractured shale formations give insight into the microbial ecology and biogeochemical conditions down-well. This study explores the potential for sulfide production by persistent microorganisms recovered from produced water samples collected from the Marcellus shale formation. Hydrogen sulfide is highly toxic and corrosive, and can lead to the formation of “sour gas” which is costly to refine. Furthermore, microbial colonisation of hydraulically fractured shale could result in formation plugging and a reduction in well productivity. It is vital to assess the potential for sulfide production in persistent microbial taxa, especially when considering the trend of reusing produced waters as input fluids, potentially enriching for problematic microorganisms. Using most probable number counts and 16S rRNA gene sequencing, multiple viable strains of bacteria were identified from stored produced waters, mostly belonging to the Genus Halanaerobium, that were capable of growth via fermentation, and produced sulfide when supplied with thiosulfate. No sulfate-reducing bacteria were detected through culturing, despite the detection of relatively low numbers of sulfate-reducing lineages by high-throughput 16S rRNA gene sequencing. These results demonstrate that sulfidogenic produced water populations remain viable for years post production and, if left unchecked, have the potential to lead to natural gas souring during shale gas extraction.